Sustainable development reporting in public sector institutions and agencies - Bistra Nikolova (Икономика и компютърни науки)
The scientific report aims to study the reporting and disclosure of sustainable development in public-sector institutions and agencies. These issues are considered in the context of the Concept of Corporate Social Responsibility (CSR), the principles of good governance, and the introduction of quality management systems (QMS) in the public sector, considering the experience of the National Revenue Agency (NRA) in Bulgaria in this direction.